2020
DOI: 10.3390/vaccines8030493
|View full text |Cite
|
Sign up to set email alerts
|

IgM+ and IgT+ B Cell Traffic to the Heart during SAV Infection in Atlantic Salmon

Abstract: B cells of teleost fish differentiate in the head kidney, and spleen, and either remain in the lymphatic organs or move to the blood and peripheral tissues. There is limited knowledge about piscine B cell traffic to sites of vaccination and infection and their functional roles at these sites. In this work, we examined the traffic of B cells in Atlantic salmon challenged with salmonid alphavirus (SAV). In situ hybridization (RNAScope) showed increased numbers of immunoglobin (Ig)M+ and IgT+ B cells in the heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The IgT + B cells comprise a separate lineage of fish B cells that appears to have a main role in mucosal surfaces such as the gut, the skin and the gills [ 13 , 15 , 19 ], and only has being extensively characterized in rainbow trout and zebrafish ( Danio rerio ) [ 4 , 10 , 18 , 21 ]. Other studies conducted in sea bass ( Dicentrarchus labrax ) [ 8 , 9 ], Atlantic salmon [ 55 , 56 ], large yellow croaker ( Larimichthys crocea ) [11] and grouper ( Epinephelus coioides ) [12] shed light over some aspects of the structural and functional characteristics of this Ig isotype. The present study describes for the first time the use of a monoclonal antibody against Nile tilapia IgT in the identification of IgT + B lymphocyte populations by flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IgT + B cells comprise a separate lineage of fish B cells that appears to have a main role in mucosal surfaces such as the gut, the skin and the gills [ 13 , 15 , 19 ], and only has being extensively characterized in rainbow trout and zebrafish ( Danio rerio ) [ 4 , 10 , 18 , 21 ]. Other studies conducted in sea bass ( Dicentrarchus labrax ) [ 8 , 9 ], Atlantic salmon [ 55 , 56 ], large yellow croaker ( Larimichthys crocea ) [11] and grouper ( Epinephelus coioides ) [12] shed light over some aspects of the structural and functional characteristics of this Ig isotype. The present study describes for the first time the use of a monoclonal antibody against Nile tilapia IgT in the identification of IgT + B lymphocyte populations by flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…Upon activation, B cells start a differentiation process that leads them to a plasmablast state, and they eventually to become plasma cells, with a greater capacity to secrete immunoglobulins (Igs) [57] . The IgT has been described as an Ig specialized in mucosal immunity [13] , but some studies reported the presence and activation of IgT + B cells in systemic compartments after viral, bacterial or parasitic challenge [ 3 , 10 , 56 , 58 ]. The effect of the enteric myxozoan parasite Enteromyxum leei on circulating Igs in gilthead sea bream ( Sparus aurata ) from a long-term infection revealed a significant increase in IgT levels in serum, which was significantly higher than IgM levels in challenged fish.…”
Section: Discussionmentioning
confidence: 99%
“…IgT found in the MALTs is known to coat mucosal pathogens and microbiota, particularly in the gut and gill to maintain mucosal homeostasis ( 12 ). Additionally, IgT + B cells have been observed to be mobilized to the infection site in-vivo ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…NSAB can be detected in the assay by binding circulating antibodies to model antigens toward which the Atlantic salmon has never been exposed. Our recent studies showed strong responses of NSAB to vaccination, functional disorders and infections with pathogens indicating their importance in Atlantic salmon [13][14][15][16]. Sequencing of the variable region of IgM heavy chain (Ig-seq) evaluates the size and complexity of the antibody repertoire [17].…”
Section: Introductionmentioning
confidence: 99%
“…Each unique sequence (clonotype) serves as a barcode for clonal B cells derived from a single progenitor cell. The sharing of identical clonotypes between tissues reflects a migration of B cells [15].…”
Section: Introductionmentioning
confidence: 99%